Optimizing productivity, energetics and economics in a rice-blackgram cropping system under variable sowing dates, establishment methods and weed management - Susmita, P; Basudev, B; Bijay, K M; Anupama, B; Rabindra, K N; Rajkumari, B; Anita, M; Ipsita, K; Suchismita, T (Plant Science Today, 2025)
A field experiment was conducted to evaluate the influence of sowing dates and crop establishment methods of Kharif rice followed by weed management methods in Rabi blackgram on the productivity, energetics and economics of a rice-blackgram (Oryza sativa-Vigna mungo) cropping system. The experiment was laid out in a split-split plot design, with four sowing dates and three establishment methods in rice and three weed management treatments in blackgram. Results of the experiment revealed that sowing rice one week after the onset of the monsoon, combined with non-puddled transplanted rice (NPTR) and post-emergence application of imazethapyr at 0.1 kg ha-1 in blackgram, significantly enhanced system rice equivalent yield (7.93 t ha-1), productivity (19.90 kg ha-1 day-1), energy use efficiency (5.74) and profitability (₹55750 ha-1 net return). Direct-seeded rice (DSR) recorded higher energy productivity of 0.25 kg MJ-1, while NPTR offered a balance between productivity and energy efficiency and recorded the maximum energy efficiency ratio of 2.84. Overall, the combination of NPTR sown one week after the onset of monsoon, followed by imazethapyr-based weed management in blackgram, proved most effective for maximizing productivity, system energetics and profitability. These findings offer valuable insights for optimizing rice-pulse based cropping systems under monsoon-dependent agro-ecosystems of coastal Odisha.